The Revaluation of All Values: Extremism, The Ultra-Left, and Revolutionary Anthropology. Issue 3 (3rd July 2018) - el-Ojeili, Chamsy; Taylor, Dylan
ABSTRACT: The notion of "extremism, " we argue, can be understood as an element of the contemporary liberal consensus or "post-politics." In particular, the anti-utopian character of extremism discourse necessitates robust critical theoretical attention. As part of this critique, we seek to return to the historic far-Left and examine various dimensions of Leftist "extremism, " reading and retrieving this material in light of its utopian significance. Here, we examine far-Left extremism that deals with the utopian re-making of the subject, what might be called the "revolutionary anthropology" found in far-Left work. Exploring some of the historic twists and turns of this revolutionary anthropology, drawing on the work of Luc Boltanski and associates, we suggest three distinctive facets of this renewed critical bearing within contemporary far-Left thought: insurrectionary immediatism, a new anti-foundationalist collectivism, and a theological turn. Attention to the sphere of revolutionary anthropology, we hope, might help us think the subject(s) able to not only resist the current social order but also to realise a new one.